PERBANDINGAN MUTU DAN PENDAPATAN PETANI UMBI PORANG KABUPATEN MADIUN PROVINSI JAWA TIMUR - Vera Ramashinta; Akhmad Mahbubi; Iwan Aminudin (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Porang is a food crop commodity that has great potential for export and is strategic in the national economy. Porang plants contain glucomannan which is widely used as a main or alternative ingredient in the food and health industry, making porang tubers have quite a high selling value and have become an export commodity. The aim of the research was to find out the benefits of implementing business plantation registration by analyzing why until now there are still many porang farmers in Madiun Regency who do not implement registration of their business plantations, by comparing the quality and income of registered porang farmers with those whose business plantations are not registered in Madiun Regency, East Java Province. The scope of the research includes the quality of porang and the income of porang farmers in Madiun Regency, East Java Province. The method used in this research is quantitative research using a survey approach through interviews using farmer questionnaires, then a t test (test) analysis is carried out to compare the two groups to be studied. The results of the research showed that there were significant differences in the quality of porang in the sub-variables of tuber color and level of damage to the tubers, while those that did not show significant differences were in the sub-variables of tuber weight and biological shape of the porang tubers. Meanwhile, the sub-variable income that shows significant differences is for production costs, production quantities, prices and income of porang farmers, both registered and unregistered, on their business plantations in Madiun Regency, East Java Province.  The average income obtained by farmers who implement business plantation registration is IDR. 30,321,772, while the average income of porang farmers who do not implement plantation registration on their business land is Rp. 6,697,130. more profitable (RC value 1.95) compared to farmers who are not registered as plantations (RC value 1.52). Keywords: Porang, Quality, Income, Registration of business land plantations